2006
DOI: 10.3167/np.2006.100202
|View full text |Cite
|
Sign up to set email alerts
|

Human-Animal Relations in Pastoralism

Abstract: Humans and Reindeer on the Move, this special issue of Nomadic Peoples. carries a challenging intent of purpose. It aims to give a state-of-the-art, comparative perspective of reindeer management spread around the circumpolar rim. Reindeer-related livelihoods encompass the topic in such diverse and multiple ways that movement becomes not only the overarching 'glue" of this special issue; it also invites us, together with the authors, to contribute theoretically to our understanding of the move. The title 'Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The adaptive capacity, vulnerability, and resilience of reindeer herding to global change have been studied in northern Fennoscandia, northwestern Russia, and Alaska in various interdisciplinary and intercultural projects (e.g., Beach and Stammler, 2006;Stammler and Beach, 2006;Tyler et al, 2007;Moen, 2008;Rees et al, 2008;Rattenbury et al, 2009;Turunen et al, 2009;Hovelsrud and Smit, 2010). It has been shown that reindeer herders' traditional responses to changes are greatly dependent on flexibility in herding practices.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive capacity, vulnerability, and resilience of reindeer herding to global change have been studied in northern Fennoscandia, northwestern Russia, and Alaska in various interdisciplinary and intercultural projects (e.g., Beach and Stammler, 2006;Stammler and Beach, 2006;Tyler et al, 2007;Moen, 2008;Rees et al, 2008;Rattenbury et al, 2009;Turunen et al, 2009;Hovelsrud and Smit, 2010). It has been shown that reindeer herders' traditional responses to changes are greatly dependent on flexibility in herding practices.…”
Section: Discussionmentioning
confidence: 99%
“…No commonly accepted definition of this term exists at this time. However, Beach and Stammler (2006) have recently claimed that this term actually refers to behavioral differences between controlled and uncontrolled reindeer. Our material supports this claim, but with an important correction.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is difficult to meaningfully extend these findings. Surprisingly, in her discussions of human-animal relations, Kazato also fails to draw upon major works on the topic, such as those by Tim Ingold (1986Ingold ( , 1988Ingold ( , 2000 or more recent articles such as Beach and Stammler (2006), which appeared in this journal.…”
mentioning
confidence: 84%